Neonatal Screening for Severe Combined Immune Deficiency in Russia: Glorious Future or Tomorrow's Reality? - Svetlana S. Deryabina; Irina A. Tuzankina; Elena V. Vlasova; Mikhail A. Bolkov; Viktor N. Shershnev ("Paediatrician" Publishers LLC, 2017)
Mass screening of newborns in Russia for five hereditary diseases does not meet the requirements of the world community for the neonatal screening program. Success in the development of laboratory diagnostic technologies and active introduction of achievements in genetics and molecular biology into medical practice allow for the revision of the list of nosologies included in the national neonatal screening program by replacing the disease or adding new nosologies. The article discusses the possibility of including genetic testing for severe combined immune deficiency in the Newborn Screening Program in Russia. The results from a retrospective study of markers of naive T- and B-lymphocytes (TREC and KREC) in the group of children with immuno-dependent pathology developed in the first year of life are discussed.